'Urban expansion and agricultural land use change in Ghana: Implications for peri-urban farmer household food security in Wa Municipality'. Issue 2 (4th May 2021) - Ziem Bonye, Samuel; Yenglier Yiridomoh, Gordon; Derbile, Emmanuel K.
ABSTRACT: Food price hikes globally re-energised investment in innovative strategies of food production including urban and peri-urban agriculture. Unfortunately, uncontrolled urbanisation have impacted gravely on food production in peri-urban areas in developing countries. This study was conducted in the Wa Municipalityto examine how peri-urban agricultural land use change impact on food security of farmers. A mixed methods study of inquiry with 235 smallholder farmers were used for the study. Questionnaires, interviews and historical information captured using the Geographic Information System (GIS) were used to collect the data. The results revealed that, hectares of agricultural land in peri-urban Wa over the last three decades has drastically lost its space to urban development through residentuial and infrastructural development. The study also found that agricultural land use change has resulted in food insecurity as the majority of the smallholder farmers were unable to meet their food needs over the last decade. The practical and policy implication of the study are discussed.